Folk Dance Revival Strategies - Nahachewsky, Andriy (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
AbstractEthnochoreologists are now more open to the study of folk dance revival groups, though they still lack common terminology or conceptual frameworks. Based upon the motivations and priorities of their participants, dance groups can be identified as “Enjoyers,” “Preservers,” “Presenters,” “Creators,” or perhaps “All-stars.” Several examples show how each of these strategies may impact on the organizational structures, dance forms and other aspects of the groups’ activities. These conceptual categories are presented with the suggestion that they may be useful for researchers, government policymakers, and dance group leaders.